Una ruptura en la ordenación del saber de las enciclopedias medievales. El "Invencionario" (1474) de Alfonso de Toledo - Fuertes Herreros, José Luis (Revista española de filosofía medieval, 1995)
If Alfonso de Toledo's encyclopedia of knowledge is situated within the encyclopedic tradition, the Invencionario, 1474, is studied, highlighting the break it made with respect to the medieval order and its encyclopedias, a break which announced a new ordering of knowledge and which manifests a change of age: the transition from the Middle Ages to the Renaissance.